Economic Policy of Renewable Energy Adoption, Economic Policy of Digital Technology, Human Resource Management, Business Decision - Ali Raza; Maryam Khokhar; Reyna Esperanza Zea Gordillo; Faisal Ejaz; Tahir Saeed Jagirani; Fodor Zita Júlia; Md Billal Hossain (International Journal of Energy Economics and Policy, 2024)
Energy fluctuations and global economic directly hit Indian Subcontinent (Geopolitically, it generally includes the countries of Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka) economy and social welfare, which are the net importer of energy sources. This study investigates the relationship between strategic petroleum reserve and welfare losses for Indian Subcontinent. The breakdown of crude oil energy supply has a significant impact on energy security & welfare losses. Oil supply security was quantified in terms of the Indian Subcontinent's oil vulnerability index (which accounts for 84 percent of global oil imports), and welfare losses based on oil supply disruption were calculated. Afghanistan is the most susceptible country in the Indian Subcontinent in terms of energy reserves, as per the composite index results, whereas India is the lowest vulnerable. Empirical findings pointed to a 30% deficit of oil supply as the cause of the most volatile pattern of oil pricing, which exacerbates the estimated welfare loss by a 40% drop in GDP, which is around $700 in the Indian Subcontinent & $9000 in the top oil-consuming countries. According to this analysis, the Indian Subcontinent should keep at least a hundred days' worth of strategic oil resources to avert social and economic losses due to oil price fluctuations.